REVEALING THE ROLE OF SELAYAR IN THE EASTERN SHIPPING AND TRADE ROUTE; ARCHAEOLOGICAL FINDS FROM AN UNDERWATER EXCAVATION ON THE BONTO SIKUYU SITE - Jusdi, Andi; Rosmawati, Rosmawati; Muhammad Akhmar, Andi; Abdullah, Abdullah; Mulyadi , Yadi; Thahir Muda, Khadijah; Darfin, Darfin (Universitas Hasanuddin, 2023)
During the 16th-19th centuries, besides exporting copra and woven fabrics, Selayar Island was a part of the shipping route called the ‘eastern route’ used by ceramic traders. This is supported by archaeological evidence found on the Bonto Sikuyu underwater site, which has been under the threat of illegal excavation, in the forms of ceramics and Chinese coins. These archaeological finds, which are dominant in the site, may help us find out where they came from. This study used a survey method by carrying out excavation on the site. During the excavation, we found 1,718 coin pieces, 299 coin chunks, 190 porcelain pieces, 5 stoneware pieces, and one ironware piece. The ceramics came from China, Annam, and Thailand. The Chinese ceramics came from the Sung dynasty (the 9th-12th centuries) and the Yuan dynasty (the 12th-13th centuries). The Annamese and Thai ceramics came from the 14th-16th centuries.